Catalyst-dependent intrinsic ring-walking behavior on π-face of conjugated polymers. Issue 10 (16th February 2017) - Mikami, Koichiro; Nojima, Masataka; Masumoto, Yui; Mizukoshi, Yoshihide; Takita, Ryo; Yokozawa, Tsutomu; Uchiyama, Masanobu
Abstract : The balance between the ring-walking process and the oxidative-addition state are key determinants of catalyst mobility in catalyst-transfer condensation polymerization. Abstract : We show that ring-walking behavior on the π-face of conjugated polymers is catalyst-dependent, and this significantly affects the composition of the products in catalyst-transfer condensation polymerization (CTCP). Systematic mechanistic study by means of density functional calculations combined with experimental verification revealed that the activation energy of the ring-walking process on the π-face and the stability of the oxidative addition state (C–M–X) are key determinants of catalyst mobility. Our findings offer a rational basis for designing innovative catalysts and monomers for CTCP.